Search for companions in visual binary systems using precise radial-velocity measurements. (31st May 2018) - Katoh, Noriyuki; Itoh, Yoichi; Sato, Bun'ei
Abstract: The frequency of triple and quadruple systems is considered to be high in the early phase of star formation. Some multiple systems decay in the pre-main-sequence phase. The multiplicity of main-sequence stars provides clues about the evolution of binary systems. This work searched for companions of five components of visual binary systems using precise radial-velocity measurements. Their radial velocities were monitored from 2007 to 2012 using the HIgh Dispersion Echelle Spectrograph (HIDES) installed on the Okayama Astrophysical Observatory (OAO) 1.88 m reflector. In combination with previous work, this work searched for companions with an orbital period of less than 9 yr for the five bodies. We found periodic variations in the radial velocities for ADS 6190 A and BDS 10966A. The radial velocities of ADS 7311 A, 31 Dra A, and 31 Dra B show significant trends. ADS 6190 A is an SB1 binary with an orbital period of 366.2 d. The minimum mass of the secondary star is 0.5^+0.7_-0.2 M_ . The radial velocity of ADS 7311 A was monitored for an observational span of 3200 d. We rejected a planetary-mass companion as the cause of a decreasing trend in the radial velocity of ADS 7311 A. This work confirmed that the periodic variation in the radial velocity of BDS 10966 A is 771.1 d. Bisector analysis did not reveal a correlation between the asymmetry of a spectral line and the radial velocity of BDS 10966 A. We rejected nonradial oscillation of the photosphere as the source of the radial velocity variation. The variation may be caused by the rotational modulation owing to surface inhomogeneity. The orbital elements of 31 Dra A derived in this paper are consistent with those in a previous paper. 31 Dra A system is an SB1 binary with a minimum mass ratio of 0.30 ± 0.08. 31 Dra B exhibits a periodic variation in radial velocity. The orbital elements derived in this work are consistent with those reported previously by others. The variation is caused by a circumstellar planet.